PLAY-BASED LEARNING CONCEPT AND DEVELOPMENT OF TEACHING AMONG KINDERGARTEN TEACHERS - Aguilar, Shylene F. (European Journal of Education Studies, 2024)
The study aims to navigate the play-based learning concept and development of teaching in private preschools. Specifically, it identifies to explore the concept of a play-based learning approach described in terms of imagination and creativity, cognitive growth, emotional and behavioral benefits, improved literacy, greater independence, and physical fitness. This includes measuring the play-based learning development of teaching in private schools in Vietnam in language and literacy development, social and emotional skills, creativity and imagination, confidence and a positive attitude towards learning, and motor skills. On the other hand, the descriptive correlative quantitative method is utilized to obtain systematic regarding information to describe the situation, population and phenomenon. Likewise, purposive sampling is employed in the study. It is the proper way of selecting the sample size where the respondents chosen have expertise and experience in teaching preschool. The study is conducted in Vietnam because the researcher is presently teaching there which serves as the basis for her study. The study comprised one hundred twenty-five (125) respondents only. Results reveal that the concept of a play-based learning approach on imagination creativity creates a combined imagination and knowledge in the school teachers' practices to stimulate children's development of learning, cognitive growth shows to promote learning development and benefits for students in an interactive environment, emotional and behavioral benefits show to boost self-esteem and joy for the preschool learners to understand better the emotions of every individual child as the center of learning improves literacy shows to develop resources and better learning on the strategy to facilitate learning actively in the trend of quality education, greater independence shows to help socialize and observe cues and interaction on the tasks among the members of the group as part of the learning process, and physical fitness shows to provide motivation on the learning process and implementation on play-based learning in the preschool level of teaching. On the other hand, play-based learning development on language and literacy development shows its best way for learning and play for preschool children on their skills literacy and skills in language, social and emotional skills show to establish the ability to maintain meaningful and healthy relationships towards each other as to support, resolve conflicts, resist negative pressure, listen, cooperate, and communicate clearly, creativity and imagination show to provide concepts for students who are prominent for nature of learning in the subject areas of competency, positive attitude toward learning shows to design and understand the issue of predicting observation on positive learning processes, motor skills show that it requires precision and control among the learners with proper knowledge of the process. Findings show that there is no significant relationship between the concept of the play-based learning approach and the play-based learning development of teaching in private schools in Vietnam among the respondents.  Article visualizations: